Effect of submandibular gland ectomy and epidermal growth factor administration on gastrointestinal tract in adult mice - Minami, Naomi; Sato, Akinao; Kashimata, Masanori; Minami, Naoyuki; Hiramatsu, Masahiko (Japanese Journal of Oral Biology, 1987)
We investigated the effect of sialoadenectomy and an epidermal growth factor (EGF) administration on the growth of gastrointestinal tract in adult mice. The removal of the submandibular gland (SMG) significantly decreased, or tended to decrease the organ weight, protein, DNA and RNA contents in the duodenum and jejunum, in both male and female mice. These decreases were restored by injection of EGF. In the stomach, the romoval of SMG had no effect on either parameter, whereas the injection of EGF significantly increased the protein, DNA and RNA contents in male mice. On the ileum, sialoadenectomy and EGF injection had no effect. From these results, it is suggested that EGF in the SMG may act as a trophic substance for the duodenum and jejunum in adult mice.